On Journalistic Texts as Sources of Scientific Inquiries - Teodorașcu, Fănel (Acta Universitatis Danubius. Communicatio, 2023)
Journalism, whose mission is to inform and to persuade the public, ought to be serious and clear. The journalist, if he wants his texts to be convincing, has to be honest and also with a personal history based on honest deeds. Nevertheless, in the past, some important names from the international press industry held that the invented piece of news is better (i.e., more profitable) than the true piece of news. For this reason, some voices stated that historians cannot use journalistic texts as sources of information for their scientific inquiries. In this article, we will try to estimate to what extent a journalist is to be of real help to a historian. In order to conduct our research, we read many journalistic texts which were published in newspapers and magazines such as “Universul”, “Viitorul”, “Rampa”, “Revista Fundațiilor Regale”, “Telegraful român” (from Sibiu), “Dimineața” etc. Most of the sources we used are referring to the period between the two World Wars from the past century.